1)
y-2x=1
6x-y=7 y=6x-7
6x-7-2x=1
6x-2x=1+7
4x=8
x=8:4
x=2
y=6*2-7
y=5
2)
x+y=6 x=6-y
3x-5y=2
3(6-y)-5y=2
18-3y-5y=2
-8y=-16
y=-16:-8
y=2
x=6-2
x=4
3)
7x-3y=13
x-2y=5 x=5+2y
7(5+2y)-3y=13
35+14y-3y=13
11y=13-35
11y= -22
y=-22:11
y=-2
x=5+2*(-2)
x=9
4)
2x+y=12 y= 12-2x
7x-2y=31
7x-2(12-2x)=31
7x-24+4x=31
11x=31+24
11x=55
x=55:11
x=5
y=12-2*5
y=2
5)
4x-y=11 y=4x-11
6x-2y=13
6x-2(4x-11)=13
6x-8x+22=13
-2x=13-22
-2x=-9
x=-9:-2
x=4,5
y=4*4,5-11
y=18-11
y=7
6)
8y-x=4 x=-4+8y
2x-21y=2
2(-4+8y)-21y=2
-8+16y-21y=2
-5y=2+8
-5y=10
y=10:-5
y=-2
x=-4+8*-2
x=-20
Объяснение:
1. a) (y-6)²=y²-12y+36
b) (7x+2)²=49x²+28x+4
в) (4c-1)(4c+1)=16c²-1
г) (2a+3b)(2a-3b)=4a²-9b²
2. a) (x-3)(x-7)-2x(3x-5)=x²-7x-3x+21-6x²+10=-5x²-10x+31
б) 4a(a-5)-(a-4)²=4a²-20a-a²-8a+16=3a²-28a+16
в) 2(m+1)²-4m=2(m²+2m+1)-4m=2m²+4m+2-4m=2m²+2
г) (a-8)²-(64+2a)=a²-16a+64-64-2a=a2-18a
3. (2-x)²-x(x+1,5)=4
4-4x+x²-x²-1,5x=4
-5,5x=4-4
-5,5x=0
x=0/-5,5
x=0
4.
а) (y²– 2а) (2а + y²)=y⁴-4a²
б) (3х² + х)²=6x⁴+6x³+x²
в) (2 + m)² (2 – m)²=(4+4m+m²)(4-4m+m²)=16-8m²+m⁴
5. Упростите выражение
(у² – 2у)² – у²(у + 3)(у – 3) + 2у(2у² + 5)=y⁴-4y³+4y²-y²(y²-9)+4y³+10y=13y²+10y